2017
DOI: 10.1080/03079457.2017.1359404
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Enterococcus faecalis isolates by chicken embryo lethality assay and ERIC-PCR

Abstract: Enterococcus faecalis is the major causative agent of amyloid arthropathy in chickens. Given the difficulty of estimating the risk from field strains, the embryo lethality assay (ELA) is proposed in this study as a model to predict the virulence of 68 avian E. faecalis strains. Additionally, Enterobacterial Repetitive Intergenic Consensus Polymerase Chain Reaction (ERIC-PCR) was used to characterize the genetic diversity of the E. faecalis strains. The ELA was performed 10 times with subsets of 7-8 E. faecalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 32 publications
2
6
0
1
Order By: Relevance
“…This may due to high relationship among these isolates in addition to the high virulence content for most isolates, only one isolate expressed single studied virulence gene, while most isolates have considerable content of virulence ability as shown in Table (1). This finding may agree to study by Blanco et al, 2018 who found ERIC-PCR didn't cluster stains according their virulence. Besides, Eaton &Gasson, 2001 andBorst et al, 2014 suggested that the molecular taxonomy of Enterococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…This may due to high relationship among these isolates in addition to the high virulence content for most isolates, only one isolate expressed single studied virulence gene, while most isolates have considerable content of virulence ability as shown in Table (1). This finding may agree to study by Blanco et al, 2018 who found ERIC-PCR didn't cluster stains according their virulence. Besides, Eaton &Gasson, 2001 andBorst et al, 2014 suggested that the molecular taxonomy of Enterococcus spp.…”
Section: Discussionsupporting
confidence: 92%
“…DNA fingerprinting by ERIC-PCR is widely applicable since ERIC primers do not exclusively target enterobacterial repetitive elements [ 45 ]. It was demonstrated that it is a reliable tool, with high discriminatory power among Enterococcus strains isolated from food [ 46 , 47 , 48 ], water samples [ 49 ], clinical specimens obtained from animals [ 50 , 51 ] and humans [ 52 ]. In previous studies, the genotyping assay directed ERIC1 or ERIC1 in combination with ERIC2 primers against E. faecalis and/or E. faecium genomes.…”
Section: Discussionmentioning
confidence: 99%
“…VRE isolates from different sources were fingerprinted using ERIC-PCR assay as described by Blanco., et al [10] modifications in order to obtain a better band pattern. ERIC-1…”
Section: Genotyping Of Vre By Eric-pcrmentioning
confidence: 99%
“…Reliable molecular typing methods for purpose of finding the relatedness between bacterial isolates have become progressively important to evaluate outbreak and endemic conditions with food borne pathogens. Different techniques like Enterobacterial Repetitive Intergenic Consensus (ERIC) PCR [10], Repetitive Extergenic Palindromic (REP) PCR [11], PFGE-Pulsed-field gel electrophoresis [12,13], determination of 16S rRNA sequences [14,15], RFLP-Restriction Fragment Length Polymorphism [16], MLST-Multilocus Sequence Typing [17][18][19][20] and AFLP-Amplified Fragment Length polymorphisms [21,22] are generally used for typing of Enterococcus spp. PCR-based techniques like REP and ERIC PCR are accurate, rapid, reproducible, sensitive, specific and reliable diagnostics, which are used for determining different DNA fingerprints [23].…”
Section: Introductionmentioning
confidence: 99%